Enantioselective dearomative ortho-cycloaddition transformation of unactivated arenes by cage-confined visible-light photocatalysis - Jie Yang; Zhongshu Li; Xiantao Wu; Jie Chen; Sisi Huang; Yu-Lin Lu; Zhiwei Jiao; Cheng-Yong Su (Nature Communications)
Abstract Photoinduced dearomatization of arenes is a powerful strategy in organic synthesis to disrupt the stable aromaticity; however, the asymmetric dearomatization photocatalysis of unactivated arenes remains highly challenging and rare. Herein we demonstrate an enzyme-mimicking cage-confined visible-light asymmetric photocatalysis method for intramolecular dearomative cycloaddition with electron-deficient β-aryl enones. Owing to the multi-functional synergy of chirality, energy transfer, and host-guest interactions in the confined microenvironments, the self-assembled chiral cage-photoreactor could pre-organize the arenes and activate the β-aryl enones to give stereoselectively fused cyclobutanes through visible-light induced [2 + 2] ortho-cycloaddition. Notably, the competing transformation to stable [4 + 2] cycloadducts has been inhibited, producing thermodynamically unfavorable [2 + 2] cycloadducts with excellent regio-, diastereo-, and enantioselectivities.